The Performance Concepts of Adu-Tandiang in Pariaman Society: Fighting, Competing, and Fighting/Competing as Main Characteristics - Asril; Rustim; Dede Pramayoza (Wacana Seni Journal of Arts Discourse, 2024)
This paper analyses the subject of adu-tandiang, which includes adu (fighting), tandiang (competing), and adu/tandiang (fighting/competing); three concepts of performance that are found in the performing arts and rituals of Pariaman society. This study uses an emic approach and grounded theory method to obtain supporting data about the concepts of adu, tandiang, and adu/tandiang. The research results show that the performing arts and traditional rituals in Pariaman are basically dynamic and always have adu-tandiang concept. The characteristics of performances with elements of adu, tandiang, and adu/tandiang are dynamic, and reflect the nature and character of the Pariaman people themselves, as a result of their history as a coastal community and facing many encounters with foreign communities. Therefore, the concepts of adu, tandiang, and adu/tandiang are generalisations of principles that characterise almost all performances in Pariaman society.